A special relationship: a broad survey of Japanese performance training methodologies' influence on Brisbane actor training since the 1990s. Issue 3 (3rd July 2021) - Neideck, Jeremy; Kelly, Kathryn
Abstract : For a small enclave of self-consciously avant-garde theatre-makers in Brisbane in the 1990s, Japanese theatre was a lodestar – an answer to what we saw as the moribund strictures of Australian naturalism. While in other theatre city-state-cultures this manifested in postdramatic director's theatre or iconoclastic experimentation, the desire to escape the past in Brisbane turned inward, to the bodies of performers. Japanese actor training emphasised embodiment, presence, and intensive and passionate training, in particular through the influential writing of Tadashi Suzuki in The Way of Acting (1986 ). Suzuki's training method has left its traces on almost all of the actor training academies in the city. It was at this time too that Hijikata's dance of darkness, butoh, started to take root. In Brisbane, this apocalyptic, image-based form of physical expression became entangled with Suzuki's method in the performative aesthetic life of the underground, and later, the main stages. The culture of physical training has had a profound impact on the making processes and the distinctive repertory of the city of Brisbane. This article explores this unique training and performance history from different perspectives in its diverse ecology as a way of understanding the hold and staying power of these traditions.